2016
DOI: 10.1053/j.ajkd.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Clinical Patterns of Nephron Hypertrophy and Nephrosclerosis Among Apparently Healthy Adults

Abstract: Background Even among ostensibly healthy adults, there is often mild pathology in the kidney. The detection of kidney microstructural variation and pathology by imaging and the clinical pattern associated with these structural findings is unclear. Study Design Cross-sectional (clinical-pathological correlation). Setting & Participants Living kidney donors at Mayo Clinic (Minnesota and Arizona sites) and Cleveland Clinic 2000-2011. Predictors Pre-donation kidney function, risk factors, and contrast comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
146
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(154 citation statements)
references
References 47 publications
5
146
0
3
Order By: Relevance
“…They found that while nephron number decreased with healthy aging, SNGFR remained relatively constant, and glomerular volume did not increase in association with nephron loss (39). They concluded that this failure to compensate for loss of nephrons in healthy aging might be due to a concurrent decrease in metabolic demand that could influence GFR (22).…”
Section: Discussionmentioning
confidence: 99%
“…They found that while nephron number decreased with healthy aging, SNGFR remained relatively constant, and glomerular volume did not increase in association with nephron loss (39). They concluded that this failure to compensate for loss of nephrons in healthy aging might be due to a concurrent decrease in metabolic demand that could influence GFR (22).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of nephrosclerosis probably explains the age-related decline in the total GFR over time. 14,15,24 Seemingly healthy persons can also have more nephrosclerosis than expected for their age, yet may not have a further reduction in the total GFR. 14,24 This study showed that nephrosclerosis exceeding that expected for age decreased the number of nephrons but was generally accompanied by a compensatory higher single-nephron GFR, which maintained the total GFR.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,24 Seemingly healthy persons can also have more nephrosclerosis than expected for their age, yet may not have a further reduction in the total GFR. 14,24 This study showed that nephrosclerosis exceeding that expected for age decreased the number of nephrons but was generally accompanied by a compensatory higher single-nephron GFR, which maintained the total GFR. The apparent failure of the single-nephron GFR to increase with the expected age-related nephron loss, whereas it increased with nephro-sclerosis beyond the level expected for age, may support an age-based approach to the identification of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed anatomic and physiologic studies of the healthiest of the healthy, normal living donors for kidney transplantation by the Mayo Clinic and Cleveland Clinic have been particularly revealing. [14][15][16][17][18][19] We are all born with a complement of nephrons determined in large part by the process of nephrogenesis in utero. 20 This process can be influenced, either negatively or positively by the maternal-fetal nexus.…”
Section: What Is the Aging Kidney?mentioning
confidence: 99%